PROJECT-BASED LEARNING IN CATERING: DEVELOPING SKILLS, CONFIDENCE, AND EMPLOYABILITY AMONG STUDENTS WITH SPECIAL EDUCATIONAL NEEDS (SENS) (Proceedings of International Conference on Special Education, 2025)
Project-based learning has gained recognition as an effective pedagogical approach that fosters practical skills and confidence among students. The Food Preparation and Production course offers the Malaysian Skills Certificate (SKM) Level 2 to Special Education Needs Students (SENs) with intellectual disabilities and learning difficulties. This action research study aimed to evaluate the effectiveness of project-based learning in catering activities in enhancing the skills and self- confidence of SENs. The study specifically addressed challenges associated with traditional buffet preparation, which was often less engaging and prone to food wastage. To mitigate these issues, the concept of a mini buffet was introduced, focusing on preparing small-sized dishes with diverse selections and creative plating techniques. Thirteen SENs participated in this study, divided into two sections: kitchen and restaurant. Data collection methods included observations, questionnaires, and students’ self-assessments. The findings indicated notable improvements in students’ technical skills, proficiency in handling kitchen equipment, time management, communication abilities, and self-confidence. Additionally, students gained a deeper understanding of the significance of preparing small-portioned dishes to minimize food waste. Regarding customer satisfaction, 95.2% of respondents agreed that the variety of small-sized dishes enhanced both visual appeal and presentation quality. Furthermore, the use of flowcharts and standardized recipes facilitated a more systematic comprehension of work processes, reducing students' reliance on teachers. In conclusion, integrating project-based learning through mini buffet activities effectively enhanced the skills, self-confidence, and employability of SENs in the catering industry while simultaneously improving teaching practices and enriching the Food Preparation and Production course.